Camel Milk is an Alternative and a Complementary Treatment to the Current Parenteral Insulin Therapy of Insulin-dependent Diabetes Mellitus - Abdalla, Kamal Omer (Gezira Journal of Health Sciences, 2018)
The main treatment of insulin-dependent diabetes mellitus (IDDM) is insulin replacement via parenteral routes which is far from satisfactory, because injection is generally a painful procedure, especially when patients need to get the injections throughout their life by 2-3 injections/day. Secondly, many patients have phobia against injections especially children. Thirdly, insulin is expensive to purchase. Fourthly, parenteral insulin is not safe in the long-term of uses as development of anti-insulin antibodies is possible, and fifthly, parenteral insulin is associated with the risk of hypoglycemic events. For those reasons, raw dromedary’s camel milk is an alternative and or complementary to pareneral insulin treatment of IDDM. This paper discusses the chemical constituents and properties of dromedary’s camel milk, recent research about its efficacy in the treatment of IDDM, its role in the restoration of experimentally damaged beta-cells of the pancreas, its role in the improvement of lipid metabolism, body mass index and functions of the kidneys and liver of subjects with IDDM received camel milk. This paper demonstrates that, raw dromedary’s camel milk causes significant reduction in insulin doses in insulin dependent diabetic subjects to obtain glycemic control along with significant hypoglycemic effects. Significant improvement were also observed in HbA1c levels, micro albuminuria, lipid metabolism, BMI, biochemical parameters of the liver and kidney functions of camel milk fed experimental subjects with IDDM. Camel milk works as a regulator of blood sugar in the absence of original insulin, and it seems to work together with the body’s own restorative and regenerative abilities to maintain normal health. Camel milk is well tolerated and its uses are not associated with the risk of hypoglycemic events, and it may be able to eliminate the alloxan and other chemicals’ induced-toxicity on pancreas and on other body’s organs via regenerative effects on damaged cells with unknown mechanism and could be used as an alternative and or a complementary treatment to current IDDM therapy.